Intracranial germ cell tumors: advancement in genomic diagnostics and the need for novel therapeutics - Yeo, Kee Kiat; Gell, Joanna; Dhall, Girish; Lau, Ching (Frontiers in Oncology, 2025)
IntroductionThe outcomes for patients with intracranial germ cell tumors (GCT) has improved over the past few decades. However, there remains a lack of a consensus on a standard diagnostic and treatment approach of these tumors. The diagnostic work-up of intracranial GCT remains variable, and the treatment for patients with recurrent disease remains challenging.MethodsWe review the current approach in the diagnosis and treatment of intracranial GCT. Given the heterogeneity of these tumors, we highlight the challenges and controversy with these conventional approaches.ResultsWe discuss the advancements in the understanding of the underlying genetic changes in intracranial GCT and the utility of novel molecular techniques in the diagnosis and classification of intracranial germ cell tumors as well as development of potential novel therapeutics.DiscussionDevelopment of liquid biopsy platforms for diagnosis and management of malignancies is a rapidly growing field. Current approach utilizing traditional tumor markers have significant limitations. In this review, we will discuss profiling of intracranial GCTs for genetic and epigenetic signatures, which are emerging as promising biomarkers to assist in the diagnosis and management of intracranial GCTs. Various studies have shown that activating mutations in MAPK pathway are common alterations in intracranial GCTs, with KIT expression seen in most germinomas. Development of targeted therapeutics against KIT has led to the prospect of targeted therapy in germinoma. Other treatment modalities being considered for clinical development include immunotherapy and the use of immune checkpoint inhibitors, especially in NGGCT. In this review, we will discuss the potential novel therapeutics and the clinical trials that are currently under development.